Herschel-ATLAS/GAMA: SDSS cross-correlation induced by weak lensing - Gonzalez-Nuevo, J.; Lapi, A.; Negrello, M.; Danese, L.; De Zotti, G.; Amber, S.; Baes, M.; Bland-Hawthorn, J.; Bourne, N.; Brough, S.; Bussmann, R.S.; Cai, Z-Y.; et al. (Oxford University Press, 2014)
We report a highly significant (>10σ) spatial correlation between galaxies with S350 μm ≥ 30 mJy detected in the equatorial fields of the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS) with estimated redshifts ≳ 1.5, and Sloan Digital Sky Survey (SDSS) or Galaxy And Mass Assembly (GAMA) galaxies at 0.2 ≤ z ≤ 0.6. The significance of the cross-correlation is much higher than those reported so far for samples with non-overlapping redshift distributions selected in other wavebands. Extensive, realistic simulations of clustered sub-mm galaxies amplified by foreground structures confirm that the cross-correlation can be explained by weak gravitational lensing (μ < 2). The simulations also show that the measured amplitude and range of angular scales of the signal are larger than can be accounted for by galaxy–galaxy weak lensing. However, for scales ≲ 2 arcmin, the signal can be reproduced if SDSS/GAMA galaxies act as signposts of galaxy groups/clusters with halo masses in the range 1013.2–1014.5 M⊙. The signal detected on larger scales appears to reflect the clustering of such haloes.